Drop-in replacement in a R134 ejector refrigeration cycle by HFO refrigerants - Fang, Yu; Croquer, Sergio; Poncet, Sébastien; Aidoun, Zine; Bartosiewicz, Yann (International journal of refrigeration, 2017)
•Numerical analysis of a supersonic single-phase ejector.•Thermodynamical study of a Heat Driven Ejector Refrigeration cycle.•Performance evaluation of three refrigerants including two HFOs.•Low-GWP R134a alternatives for drop-in replacement. The present work reports a numerical analysis of a single-phase supersonic ejector working with R134a as well as hydrofluoroolefin (HFO) refrigerants R1234yf and R1234ze(E). Comparisons were made regarding the ejector performances under varying operating conditions and refrigerant mixture proportions. The calculations have been then extended to an existing ejector heat driven refrigeration cycle (EHDRC). R1234yf appears to be a good candidate for drop-in replacement of R134a in a real EHDRC, while using R1234ze(E) would induce some modifications due to its thermodynamic properties. Maintaining the same pressure ratio for the ejector would lead on one hand to better entrainment ratio using R1234ze(E) and on the other hand to reduced coefficient of performance (COP) and cooling power by 4.2% and 26.6% in average, respectively. Using R1234yf under the same conditions induces a decrease of 5.2% for the entrainment ratio, 9.6% for the COP and 19.8% for the cooling power in average.